Research Domain Criteria as Psychiatric Nosology: Conceptual, Practical and Neuroethical Implications - Akram, Faisal (Cambridge quarterly of healthcare ethics, 2017)
Diagnostic classification systems in psychiatry have continued to rely on clinical phenomenology, despite limitations inherent in that approach. In view of these limitations and recent progress in neuroscience, the National Institute of Mental Health (NIMH) has initiated the Research Domain Criteria (RDoC) project to develop a more neuroscientifically based system of characterizing and classifying psychiatric disorders. The RDoC initiative aims to transform psychiatry into an integrative science of psychopathology in which mental illnesses will be defined as involving putative dysfunctions in neural nodes and networks. However, conceptual, methodological, neuroethical, and social issues inherent in and/or derived from the use of RDoC need to be addressed before any attempt is made to implement their use in clinical psychiatry. This article describes current progress in RDoC; defines key technical, neuroethical, and social issues generated by RDoC adoption and use; and posits key questions that must be addressed and resolved if RDoC are to be employed for psychiatric diagnoses and therapeutics. Specifically, we posit that objectivization of complex mental phenomena may raise ethical questions about autonomy, the value of subjective experience, what constitutes normality, what constitutes a disorder, and what represents a treatment, enablement, and/or enhancement. Ethical issues may also arise from the (mis)use of biomarkers and phenotypes in predicting and treating mental disorders, and what such definitions, predictions, and interventions portend for concepts and views of sickness, criminality, professional competency, and social functioning. Given these issues, we offer that a preparatory neuroethical framework is required to define and guide the ways in which RDoC-oriented research can—and arguably should—be utilized in clinical psychiatry, and perhaps more broadly, in the social sphere.